Immune Response of Rainbow Trout (Oncorhynchus mykiss) to Selected Antigens of Yersinia ruckeri - Ispir, Unal; Gokhan, H. Bayram; Ozcan, Mikail; Dorucu, Mustafa; Saglam, Naim (Veterinarni A Farmaceuticka Univerzita Brno, 2009)
In this study, effects of Yersinia ruckeri antigens on the immune mechanisms of rainbow trout (Oncorhynchus mykiss) were examined. The weight of the 120 fish used in this study was 20-30 g. After injecting 1 mg of formalin-inactivated whole cells (FKC) and O-antigen (Ag-O) intraperitoneally, blood was taken from the caudal vein of anaesthetized fish and metabolic activity of leukocytes (Nitroblue tetrazolium (NBT) activities), phagocytic activity (PA), phagocytic index (PI), serum protein and serum total immunoglobulin (TIg) levels were determined on day 30 after the first immunization. The same procedure was conducted in the control group. In all the experimental groups, considerable increases in the immune indicators were found and significant differences detected between the control and experimental groups (p < 0.05). Metabolic activity of leukocytes decreased significantly (p < 0.05) during the following treatment with antigens compared to the control fish group.
Keywords: Rainbow trout; antigen; phagocytosis; Yersinia ruckeri; immunity